Cancer Burden in the Red Sea State, Sudan: A Ten Years of Incidence, Distribution, and Trends: (2016 - June 2025) - Widaa, Awad Abdalla (Journal of medical and pharmaceutical sciences, 2025)
Cancer is an increasing health concern in the Red Sea State while population-based data remain scarce. Aim: To describe adult cancer incidence, geographic distribution and trends in the Red Sea State between 2016 and 30 June 2025 and to assess the impact of the April 2023 armed conflict and patient displacement on registry measures. Patients and Methods: A descriptive retrospective review of all histopathologically confirmed adult cancer cases registered at Port Sudan Oncology Centre (POC) from 2016 to 30 June 2025 (n=3,265). Demographic and clinical data were abstracted from paper and electronic records; analyses used SPSS v20 to compute frequencies, age- and sex-specific and age-standardized rates; chi-square test evaluated associations (p
Keywords: Cancer incidence; prevalence; epidemiology; tumors; Red Sea State; Port Sudan Oncology Centre; displacement; armed conflict